DIGITAL TECHNOLOGIES IN MODERN EDUCATION - G‘aybullayeva Zilola Muzaffar qizi,; Nazrullayeva Farangiz, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: this passage examines the growing role of digital technologies in modern education and their impact on teaching and learning. Innovations such as e-learning  platforms,  virtual  classrooms,  AI  tools,  and  interactive  software  are transforming  traditional  education  by  increasing  accessibility,  engagement,  and collaboration. Recent reforms, including online and blended learning, have enhanced personalized learning and teacher development. Digital education also promotes better learning outcomes, lifelong learning, and prepares students for a technology-driven workforce. Despite challenges in infrastructure and digital literacy, the adoption of digital  technologies  continues  to  modernize  education  and  strengthen  its  global competitiveness.